Mundell-Tobin Effect and the Long-Run Relationship between Nominal Interest Rates and Inflation : A case of the Czech Republic - Kozák, Tomáš (2022)
The primary goal of the thesis is to empirically test the validity and magnitude of the Fisher effect or, alternatively, the Mundell-Tobin effect, in the Czech Republic during years 2004-2020, using the standard time series methodological framework. Empirical findings of this thesis document that the Fisher effect is non-existent, regardless of the used proxy variable for the expected rate of inflation. Furthermore, empirical findings also document that the Mundell-Tobin effect is present only in case of the perfectly anticipating economic agent, who can accurately predict the future values of the inflation rate. However, this assumption is not quite realistic, and therefore the presence of the Mundell-Tobin effect must be perceived with substantial limitations. Deviating from the perfect foresight assumption, the Mundell-Tobin effect is non-existent. Statistical evidence also provides a support for the statement that the real interest rate is not constant, it is influenced by persistent changes in the money supply growth rate, and therefore the long-run super-neutrality of money does not hold.